سوسيوتنظيمية تكنولوجيا المعلومات " قراءة لمتطلبات الرشاقة المنظمية " - بلوم اسمهان; شباح مريم (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
جدلية تكنولوجيا المعلومات نشوءا، مصادرا، تكوينا واستثمارا، تثير نظرة أولية تحمل ملامح الوصف السوسيوتنظيمي الذي يتغذى من روافد المقولات النظرية والممارسات العينية، المنتمية للنماذج الشاخصة للرشاقة المنظمية، الكاشفة بل المضمنة لتكنولوجيا المعلومات كلغة للسياقات المنظمية القيادية، وكقاعدة مرجعية للانطلاق في مجال الفعالية والتحسين المستمر لأداء العمليات الإدارية على السياق التنظيمي .إن موضوع الورقة البحثية الموسوم بـ : " سوسيوتنظيمية تكنولوجيا المعلومات " قراءة لمتطلبات الرشاقة المنظمية. " يعد محاولة رائجة في الفكر التنظيمي، المعزز لاستخدامات تكنولوجيا المعلومات والتقنيات الحديثة في أدائها الكاشف عن أبعاد التنمية المنظمية، والمزيد من التماثل التنظيمي لبناء آليات الحس المنظمي . الكلمات المفتاحية: سوسيوتنظيمية ، تكنلوجيا المعلومات ، الرشاقة المنظمية، التماثل التنظيمي. Summary The information technology dialectic, in its emergence, sources, formation and investment, raises an initial look that carries the features of the socio-organizational description, that feeds from the tributaries of theoretical statements and concrete practices, belonging to the distinct models of organizational agility, revealing and also embedded the information technology, as a language for leadership organizational contexts, and as a reference base for launching in the field of effectiveness and continuous improvement of the administrative operations performance, on the organizational context. This research paper enhances the uses of information technology and modern technics, in its performance revealing the dimensions of organizational development, that enhance for more organizational symmetry, to build the organizational sense mechanisms inhibiting the culture of introversion